Anatomic Features of the Tibial Plateau Predict Outcomes of ACL Reconstruction Within 7 Years After Surgery. Issue 2 (February 2019) - Kiapour, Ata M.; Yang, Daniel S.; Badger, Gary J.; Karamchedu, Naga Padmini; Murray, Martha M.; Fadale, Paul D.; Hulstyn, Michael J.; Shalvoy, Robert M.; Fleming, Braden C.
Background: Multiple anatomic features of the femoral condyles and tibial plateau have been shown to influence knee biomechanics and risk of anterior cruciate ligament (ACL) injury. However, it remains unclear how these anatomic factors affect the midterm outcomes of ACL reconstruction. Hypothesis: Decreased femoral notch width, increased posterior and coronal slopes, and decreased concavity of the tibial plateau are associated with inferior clinical, patient-reported, and osteoarthritis-related outcomes 7 years after ACL reconstruction. Study Design: Cohort study; Level of evidence, 3. Methods: Prospectively collected data from 44 patients who did not have a subsequent graft or contralateral ACL failure within 7 years after unilateral ACL reconstruction were reviewed (mean ± SD age, 23.7 ± 9.2 years; 64% women). Notch width (after notchplasty), posterior slopes of the medial and lateral tibial plateau, maximum depth of the medial tibial plateau, and coronal tibial slope were measured from magnetic resonance images. Anatomic predictors of side-to-side differences in anterior-posterior knee laxity, Knee injury and Osteoarthritis Outcome Score (KOOS), medial joint space width, and side-to-side differences in Osteoarthritis Research Society International (OARSI) x-ray score, measured at 7 years, were identified with linear regression (bivariate) and stepwise regression (multivariate). Results: Increased posterior slope of the lateral tibial plateau was associated with increased side-to-side difference in knee laxity (bivariate model only), increased side-to-side difference in the OARSI score, and decreased KOOS subscores ( R 2 > .10, P < .05). Increased posterior slope of the medial tibial plateau was associated with a higher side-to-side difference in the OARSI x-ray score (bivariate model only) and lower KOOS subscores ( R 2 > .11, P < .03). Increased coronal tibial slope was associated with lower KOOS subscores ( R 2 > .11, P < .03). Decreased medial tibial depth was associated with increased knee laxity as well as decreased KOOS subscores (ie, quality of life and symptoms; R 2 > .12, P < .03). Postoperative notch width was not a significant predictor for any surgical outcome. None of the anatomic features were predictive of medial joint space width narrowing. Conclusion: Results partially support the hypothesis and highlight the importance of knee anatomy on several outcomes of ACL reconstruction among patients without subsequent graft or contralateral ACL injures. Increasing slopes in the coronal and sagittal planes with decreasing concavity of the medial tibial plateau lead to less favorable outcomes 7 years after surgery.